Factors influencing students preferences towards e-commerce textbook purchase at university / Nur Erma Izzaty Mazlan - Mazlan, Nur Erma Izzaty (Faculty of Business and Management, 2017)
The purpose of this study is to examine the factors influencing student’s preferences towards e-commerce textbook purchase in university Malacca City Campus. This study will be based on the elements of technology acceptance model which are reliability, perceive ease of use, perceived usefulness and quality of information. The researcher focuses only at students in University Malacca City Campus. The sampling technique use in this research is sampling systematic in this research. Therefore 300 sample size. Data analysis may involve determining consistent patterns and summarizing the appropriate details revealed with the study in running and analysing data gained in this study, using Statistical Package for Social Science (SPSS) in order to key in data, analyse and formulate the data collected from the respondents via questionnaires. The codding of the data will be done manually before the process of key in data could be done by using the software.